The science, technology, society with and innovation in the higher education system. - Piedra Chávez, Ketty (Revista Universidad de Guayaquil, 2012)
The scientific revolution of the century has left us an ocean of doubts and uncertainties that science, technology, society and innovation must be urgently addressed to dace the future which will contribute to build and implement new paradigms. Paradigms that support the higher education system that becomes the universities in a knowledge society in an innovative learning organization and network organization, leading a new academic culture in which the old knowledge begets the new ,the old science is going to transfer to the new, through an accumulative process led by a motor : An academic scientific researcher in the higher education System , who must appropriate of a scientific humanist culture with social technology perspective.
Keywords: Science; technology; society and innovation; higher education system